Effects of low-molecular-weight Rehmannia glutinosa polysaccharides on p53 gene expression - Wei Xiao-Long; Ru Xiang-Bin (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of low-molecular-weight Rehmannia glutinosa polysaccharides (LRPS) on p53 gene expression. METHODS: The level of p53 gene expression was determined by quantitative polymerase chain reaction and autoradiography. RESULTS: The levels of p53 mRNA in Lewis lung cancer tissue were 0.46, 1.52, 1.48, and 1.60 respectively after saline, LRPS 20 and 40 mg.kg-1, and cyclophosphamide 10 mg.kg-1, which were the effective doses inhibiting the growth of tumor tissue cells in vivo. LRPS markedly increased p53 gene expression. CONCLUSION: LRPS effect on p53 gene expression is one of the mechanisms of antitumor activity.